CLUSTER MECHANISM OF METALS CRYSTALLIZATION - N. K. Tolochko; A. A. Andrushevich (Литьë и металлургия)
The regularities of metal crystallization, in particular, the dependence of melt critical overcooling on preliminary overheating conditions are investigated theoretically taking into account modern conception of melt cluster structure. The peculiarities of crystallization process following immediately after melting process without melt overheating are considered.